Analisis Persepsi Mahasiswa Pendidikan Matematika Terhadap Kesesuaian Antar Ayat Al-Qur’an dan Konsep Matematika (Studi Kasus di Prodi Matematika UIN Sunan Klijaga Yogyakarta) - Nurhadiningtyas, Trianita; Mujahid, Mujahid; Sabarudin, Sabarudin (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2025)
This study examines the perceptions of Mathematics Education students of UIN Sunan Kalijaga Yogyakarta regarding the relationship between mathematical concepts and spiritual values contained in the Qur'an. A qualitative approach with a case study design was used to explore students' in-depth understanding through interviews, observation, and documentation. The results showed that most students viewed order, symmetry, and logic in mathematics as a representation of God's greatness. However, some students still doubt this relationship, mainly due to the lack of relevant teaching materials and in-depth teaching approaches. Factors that influence students' perceptions include religious background, lecturers' teaching strategies, availability of teaching materials, and previous learning experiences. In addition to providing new insights into the relationship between science and religion, this study revealed that the integration of Islamic values in mathematics learning can improve students' learning motivation and spiritual character building.